Morphological features of the photoplethysmographic signal: a new approach to characterize the microcirculatory response to photobiomodulation - Ovadia-Blechman, Zehava; Hauptman, Yermiyahu; Rabin, Neta; Wiezman, Gal; Hoffer, Oshrit; Gertz, S. David; Gavish, Benjamin; Gavish, Lilach (Frontiers in Physiology, 2023)
Introduction and Objectives: Advanced analysis of the morphological features of the photoplethysmographic (PPG) waveform may provide greater understanding of mechanisms of action of photobiomodulation (PBM). Photobiomodulation is a non‐ionizing, red to near-infrared irradiation shown to induce peripheral vasodilatation, promote wound healing, and reduce pain. Using laser Doppler flowmetry combined with thermal imaging we found previously in a clinical study that PBM stimulates microcirculatory blood flow and that baseline palm skin temperature determines, at least in part, why some individuals respond favorably to PBM while others do not. ‘Responders’ (n=12) had a skin temperature range of 33°C-37.5°C, while ‘non-responders’ (n=8) had ‘cold’ or ‘hot’ skin temperature (<33°C or >37.5°C respectively). The continuous PPG signals recorded from the index fingers of both hands in the original clinical study were subjected to advanced post-acquisitional analysis in the current study, aiming to identify morphological features that may improve the accuracy of discrimination between potential responders and non-responders to PBM. Methods: The PPG signals were detrended by subtracting the lower envelope from the raw signal. The Root Mean Square (RMS) and Entropy features were extracted as were two additional morphological features -- Smoothness and number of local extrema per PPG beat (#Extrema). These describe the signal jaggedness and were developed specifically for this study. The Wilcoxon test was used for paired comparisons. Correlations were determined by the Spearman correlation test (rs). Results: The PPG waveforms of responders to PBM had increased amplitude and decreased jaggedness (Baseline vs 10’ post-irradiation: Entropy, 5.0±1.3 vs 3.9±1.1, p=0.012; #Extrema, 4.0±1.1 vs 3.0±1.6, p=0.009; RMS, 1.6±0.9 vs 2.3±1.2, p=0.004; Smoothness, 0.10±0.05 vs 0.19±0.16, p=0.016). In addition, unilateral irradiation resulted in a bilateral response, although the response of the contralateral, non-irradiated hand was shorter in duration and lower in magnitude. Although subjects with ‘cold,’ or ‘hot,’ baseline skin temperature appeared to have morphologically distinct PPG waveforms, representing vasoconstriction and vasodilatation, these were not affected by PBM irradiation. Conclusions: This pilot study indicates that post-acquisitional analysis of morphological features of the PPG waveform provides new measures for the exploration of microcirculation responsiveness to PBM.